1163. Age, Poverty and Inequity are Key Determinants of Dengue Severity in Colombia. (15th December 2022) - Acevedo-López, Doménica; Cardona-Ospina, Jaime A; Molton, Mia; Collins, Matthew H; Rodríguez-Morales, Alfonso J; Álvarez-Amaya, Valeria; Díaz-Henao, William; Ramírez, Daniel; Rojas-Gallardo, Diana; Castañeda, Camilo
Abstract: Background: Age has been a major risk factor for death and complication due to dengue infection (DENV). Although antibody-dependent enhancement (ADE) has been proposed as an explanation, other variables could shape disease outcomes. We aimed to analyze the role of age as a risk factor for disease severity across departments (ﬁrst administrative level), and epidemic years in Colombia considering poverty and inequity indexes. Methods: We conducted a retrospective study analyzing DENV epidemiological data from Colombia between 2012 to 2017, and monetary poverty, extreme poverty, and GINI indexes. Total cases, incidence, incidence of severe DENV, mortality, case- fatality rates (CFR), and complication rates (CR) were calculated for each department and year. The effect of age, department, year of infection, monetary poverty, extreme poverty, and GINI on CR and CFR was evaluated by using a generalized additive model. Results: After adjustment, age (p< 0.001), GINI (p< 0.001), monetary poverty (p< 0.001), and extreme poverty(p< 0.001) indexes were signiﬁcantly associated with the CR, but age was the only variable signiﬁcantly associated with CFR (p< 0.001). Our results revealed a ﬁrst peak of CR in patients younger than 5 years old, the second peak in patients between 27 to 34 years old, and a third peak after 45 years old. Conclusion: Our work has important implications for future designing of human cohorts analyzing the risk of complications in adults and provides evidence for improving clinical DENV risk assessment. Our ﬁndings are consistent with similar observations linking ADE with severe DENV in childhood and suggest protective antibody decay during adulthood. The interplay of biological and socioeconomic factors shaping clinical outcomes in DENV is complex and should be further analyzed Disclosures: All Authors : No reported disclosures.